Study of Quality Control of A Survey Work in Construction Projects Case Study ( AL Rahman Mosque) - N. Sayle, Khmis; A. Al- Janabi, Ibrahim (Anbar Journal of Engineering Sciences, 2008)
Recently our country is witnessed an implementation of many construction with high stories . thus , the accuracy of implementation and monitoring of survey works should be consider . in this paper quality control in survey works in AL-RAHMAN Mosque were studied as a case study . The magnitude and correlation of errors are importance to the design stage, measuring and adjustment development .in the design stage the study of errors is very important to provide us the basic chose of fingers , selection of instrument types, and proper procedures to get the specified accuracy , in the measuring sate the stud of errors is an important because it give us acceptation or rejection limitation in the site. In the adjustment operation the study of errors give us an increment in can riddance level the result of present paper indicated that there are conclusion and recommendation should be considered to accept or reject in future works.